Quo Vadis the Jakarta Special Regional Bill: Ideal Design Based on Constitutional Law Prespective - Diana; Matheus, Juan; Nugroho, Hizkia Ivan (Journal of Constitutional and Governance Studies, 2024)
The ratification of the IKN Law implies huge changes in the status of Jakarta, which was originally a special capital city into a special region with the status of a national economic center, global city, and agglomeration area. A new regulation is needed to rule this alteration. This has been responded by the House of Representatives of the Republic of Indonesia by drafting the DKJ Bill to date. However, the DKJ Bill caused many polemics about the status and position of Jakarta later. This study aims to examine the ideal design of the Jakarta Special Region Bill. This research uses a type of normative juridical research by examining various secondary data obtained through library research. The author uses a statutory approach and a conceptual approach. Based on the discussion, the DKJ Bill was drafted hastily, lack of public participation, and lack of public transparency with several provisions contradict to the spirit of regional autonomy. Although Jakarta will no longer be the capital city of Indonesia, Jakarta will be projected as an area devoted to being a business center and agglomeration with an autonomous regional government; in accordance with Article 18B of the 1945 NRI Constitution which is interpreted by the Constitutional Court in Decision Number 81/PUU-VIII / 2010. Therefore, the Government of Indonesia and the House of Representatives of the Republic of Indonesia must improve the bill a quo by implementing meaningful participation principle to emphasize the origin and characteristics of the region and the special status of Jakarta. Keywords: New Capital City of Nusantara, IKN Law, DKJ Bill. Abstrak Pengesahan UU IKN memiliki implikasi yang serius atas status Jakarta yang semula merupakan ibu kota khusus, berubah menjadi daerah istimewa dengan status pusat ekonomi nasional, kota global, dan kawasan aglomerasi. Terkait dengan perubahan status Jakarta tersebut, maka perlu dibuat suatu peraturan baru untuk mengaturnya. DPR RI telah merespon dengan menyusun RUU DKJ. Namun, RUU DKJ tersebut menimbulkan banyak polemik menyangkut status dan kedudukan Jakarta di masa yang akan datang. Penelitian ini bertujuan untuk mengkaji desain ideal RUU Daerah Istimewa DKI Jakarta. Penelitian ini merupakan penelitian yuridis normatif dengan mengkaji berbagai data sekunder yang diperoleh melalui studi kepustakaan, dengan pendekatan perundang-undangan dan konseptual. Berdasarkan hasil analisis dapat disimpulkan bahwa, RUU DKJ disusun secara tergesa-gesa, kurang melibatkan partisipasi publik, dan tidak transparan serta terdapat ketentuan di dalamnya yang bertentangan dengan semangat otonomi daerah. Meskipun Jakarta tidak lagi menjadi ibu kota Indonesia, Jakarta akan diproyeksikan sebagai daerah otonomi yang dikhususkan sebagai pusat bisnis dan aglomerasi; sesuai dengan ketentuan Pasal 18B UUD NRI 1945 sebagaimana telah ditafsirkan oleh Mahkamah Konstitusi dalam Putusan Nomor 81/PUU-VIII/2010. Oleh karena itu, Pemerintah dan DPR RI harus memperbaiki RUU a quo dengan menerapkan prinsip partisipasi yang bermakna untuk mempertegas asal usul dan karakteristik daerah serta status istimewa Jakarta. Kata kunci: Ibu Kota Baru Nusantara, UU IKN, RUU DKJ